2022
DOI: 10.1111/ffe.13684
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microstructure and cyclic behavior of 316L stainless steel obtained by Laser Powder Bed Fusion

Abstract: In this work, stainless steel 316L obtained by Laser Powder Bed Fusion (L-PBF) has been produced and characterized. The experimental campaign focuses on the samples in the as-built state under cyclic tension-compression loadings. Low cycle fatigue (LCF) and high cycle fatigue (HCF) tests are carried out. Microstructure observations are performed before and after the loadings. As-built L-PBF 316L has a good LCF performance despite the presence of surface defects but a low fatigue limit in the HCF regime. Removi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…[62][63][64] The literature data are shown in Figure 12B and agrees well with our experimental data, especially for longer lifetimes. Therefore, for higher lifetimes, defects seem to have higher detrimental impact on fatigue resistance, 65 as the gap between SLM_Chess fatigue strength and SLM_Rot or SLM_SR ones is higher for longer lifetimes. However, for short lifetimes (N < 10 5 ), the fatigue resistance of specimens with fatigue cracks initiating from the LoF (SLM_Chess) is comparable to that of the specimens where cracks initiate from the persistent slip band (PSB) in the microstructure (SLM_Rot and SLM_SR).…”
Section: Fatigue Behaviormentioning
confidence: 99%
“…[62][63][64] The literature data are shown in Figure 12B and agrees well with our experimental data, especially for longer lifetimes. Therefore, for higher lifetimes, defects seem to have higher detrimental impact on fatigue resistance, 65 as the gap between SLM_Chess fatigue strength and SLM_Rot or SLM_SR ones is higher for longer lifetimes. However, for short lifetimes (N < 10 5 ), the fatigue resistance of specimens with fatigue cracks initiating from the LoF (SLM_Chess) is comparable to that of the specimens where cracks initiate from the persistent slip band (PSB) in the microstructure (SLM_Rot and SLM_SR).…”
Section: Fatigue Behaviormentioning
confidence: 99%
“…Low-cycle and high-cycle fatigue tests have been performed on 316L steel samples produced by laser powder bed fusion technique, and a correlation between microstructure and cyclic mechanical behavior has been obtained. [14] 316L revealed a good performance under low-cycle fatigue tests, but surface defects on the sample have shown to be detrimental to the fatigue limit in the high-cycle fatigue regime. Microstructure observations of samples under low-cycle fatigue tests have revealed that local plastic deformations influence material behavior by slip steps but lack-of-fusion defects limit the high-cycle fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only a few, and often incomparable results, can be found in the literature for this additively manufactured material. For instance, fundamental studies of the LCF performance of L‐PBF AISI 316L can be found concerning the influence of: the following thermal treatment, 17,18 specimen geometry, 19 microstructure, 20 coating, 21 layer orientation, surface roughness, 22 process parameters, 23 and high strain ranges 24 . Other further studies focused their attention on the deformation mechanisms involved during cyclic loading to reveal the role of the cell structure, which distinguishes the as‐built microstructure of some AM alloys, on the LCF strength 25 .…”
Section: Introductionmentioning
confidence: 99%